Building a European identity : France, the United States, and the oil shock, 1973-1974 - Gfeller, Aurélie Elisa, 1977- (Berghahn monographs in French studies, 2012)
The Arab-Israeli war of 1973, the first oil price shock, and France's transition from Gaullist to centrist rule in 1974 coincided with the United States' attempt to redefine transatlantic relations. As the author argues, this was an important moment in which the French political elite responded with an unprecedented effort to construct an internationally influential and internally cohesive European entity. Based on extensive multi-archival research, this study combines analysis of French policy making with an inquiry into the evolution of political language, highlighting the significance of th.